Multilevel Analysis of Information Motivation Behavioral Skill Models and Its Effect on Tertiary Preventive Behavior in Elderly with Type II Diabetes Mellitus - Alimah Ulfah Khairiyyah; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Health Promotion and Behavior, 2024)
Background: Diabetes Mellitus (DM) is an important health condition for the elderly population, about a quarter of people over the age of 65 suffer from diabetes. Complications of type 2 diabetes increase the risk of death for sufferers. Complications and death from type 2 diabetes can be prevented by implementing tertiary preventive behavior. This study aimed to determine the influence of Integrated services post and other factors on tertiary preventive behavior for type 2 diabetes, using information motivation behavioral skill models theory. Subjects and Method: A cross-sectional study was conducted at 25 Integrated services post in Sukoharjo Regency, Central Java from October to November 2023. A total of 200 elderly patients with type II DM were selected by the stratified random sampling. The dependent variable is tertiary preventive behavior. The independent variables used are information, motivation, behavioral skills, age and gender. Data collection was carried out by interviews and questionnaires. Data analysis uses multilevel multiple linear regression analysis. Results: Tertiary preventive behavior is positively related to motivation (b= 0.31; 95% CI= 0.01 to 0.61; p= 0.037), behavioral skills (b= 0.74; 95% CI= 0.43 to 1.05; p= 0.001). Tertiary preventive behavior was positively related to information but was not statistically significant (b= 0.01; 95% CI= -0.30 to 0.32; p= 0.945). Tertiary preventive behavior was negatively related to age but was not statistically significant (b= -0.04; 95% CI= -0.11 to 0.01; p= 0.168) and gender (b= -0.07; 95% CI= -0.98 to 0.83; p= 0.878). Integrated services post has a contextual influence on tertiary preventive behavior in elderly patients with type-II DM (ICC= 35.99%). Conclusion: Tertiary preventive behavior in elderly patients with type 2 DM increases with good information, strong motivation and good behavioral skills. Integrated services post has a contextual effect on tertiary preventive behavior in type 2 DM patients.